COVID-19 impact on the sport sector economy and athletic performance - Wiltshire, H. D.; Supriya, R.; Baker, J. S. (Journal of Risk and Financial Management, 2022)
As COVID-19 continues to impact global health, and educational, financial, commercial institutions, sport, in particular, has not been spared. A number of major games, fixtures and competitions have been cancelled or postponed, disrupting governing bodies, organisers, teams, and athletic performers and preventing the continuous streaming of live sport, something the global sporting audience has become accustomed to (Deloitte 2020). A detailed article entitled `2020: The Year in Sports When Everyone Lost` appeared in the New York Times on 13 December. The article reported losses of USD 13 billion in the US sporting leagues, while some of Europe`s largest football clubs reported revenue losses exceeding EUR 1 billion. The outcomes were equally disastrous in other sub-sectors of sport, including Wimbledon and the Olympics (Sato et al. 2020; Skinner and Smith 2021).